Whole-Genome Sequencing and Target Validation Analysis of Müllerian Adenosarcoma: A Tumor With Complex but Specific Genetic Alterations - Ban, Yanli; Fischer, Jean V.; Maniar, Kruti P.; Guo, Haiyang; Zeng, Chang; Li, Yinuo; Zhang, Qing; Wang, Xinkun; Zhang, Wei; Bulun, Serdar E.; Wei, Jian-Jun (Frontiers in Oncology, 2020)
Mullerian adenosarcoma (MAS) is a biphasic tumor with malignant stroma. It is most commonly of endometrial origin but occasionally originates in the cervix, ovary, or other pelvic/peritoneal sites. The typical MAS is low grade with an indolent clinical course; however, tumors with sarcomatous overgrowth (SO) or a high-grade sarcoma tend to be aggressive. Tumor etiology is largely unknown. To better understand the global genome alterations and gene mutations in MAS, whole-genome sequencing (WGS) and target validation analysis were performed. MAS showed remarkable chromosome (chr) copy number variation (CNV), specifically, gains in chr 1q, 5p, 12p, 12q, and 17q and losses in chr 3p, 3q, 9p, and 11q. Gain of chr 12q13-15 was present in 50% of cases. The selected gene products in gain regions were upregulated as measured by immunohistochemistry. HMGA2 overexpression was significantly correlated with SO. While the structural variation (SV) rate was relatively low overall, a disproportionally high rate of break-ends at chr 7 was noted involving 6 in-frame rearrangement fusion genes. Among 40 frequently mutated genes detected by WGS and validated in 29 MAS by next generation sequencing (NGS), KMT2C, and BCOR were frequently seen in MAS both with and without SO, while MAGEC1 and KDM6B were strongly associated with SO. Overall, a higher rate of frequently mutated genes was found in MAS with SO (33%) than MAS without (11%). This study uncovers the complex and specific genetic alterations in this malignancy. The findings provide a tool for future investigation of these molecular changes in tumorigenesis and target therapies.